Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Pengolahan Bahan Bekas Pada Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal Banyuwangi - Nuryanah Nuryanah; Hariyanti Hariyanti; Helen F Sinambela; Widaningsih Widaningsih (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Fine motor stimulation is an important aspect of early childhood development. If a child has not been able to develop his fine motor skills well, then the child will also experience difficulty in carrying out activities related to hand skills. The aim of this research is to improve fine motor skills through used material processing activities in children aged 5-6 years at the Aisyiyah Bustanul Athfal Kindergarten, Banyuwangi. Specifically, the used material used during the research was waste paper. This type of research is classroom action research. This research was carried out in two cycles and each cycle was held in two meetings. This research was carried out at the Aisyiyah Bustanul Athfal Banyuwangi Kindergarten with research subjects being Group B aged 5-6 years, totaling 16 people. Data collection in this research used observation and documentation techniques. From cycle 1 to cycle II, especially in the